Interexaminer agreement in caries radiographic diagnosis by conventional and digital radiographs Avaliação interexaminadores no diagnóstico de cáries por meio de radiografias convencionais e digitais - Anna Sílvia Penteado Setti da Rocha; Solange Maria de Almeida; Frab Norberto Bóscolo; Francisco Haiter Neto (Journal of Applied Oral Science, 2005)
The purpose of this research was to compare two digital storage phosphor systems and conventional film, as well as verify the interexaminer agreement in radiographic diagnosis on occlusal and proximal cavities. Two digital systems and conventional radiographic film were used to evaluate 144 tooth surfaces with and without cavities; the radiographs were analyzed and scored in a scale of 4 points. Thirteen undergraduates and an oral radiologist participated as examiners. A light microscopy analysis was accomplished in order to validate the research. The results showed that there was no significant difference between the radiographic systems, however all of them had significant differences when compared to light microscopy, except for the Digora system on the proximal surface when the radiologist was the examiner. In the interexaminer evaluation, a moderate agreement level was obtained, and a fair to moderate level was obtained between the students and the oral radiologist. Regarding the validation (sensitivity, specificity, positive predict and negative predict) the values were similar between students and the oral radiologist, except for the sensitivity value on the occlusal surface. The students had the highest number of false-positive results and the oral radiologist the highest number of false-negative results. O objetivo desta pesquisa foi comparar dois sistemas digitais de armazenamento de fósforo e filme convencional, assim como verificar a concordância interexaminadores em diagnóstico radiográfico de cáries oclusais e proximais. Dois sistemas radiográficos digitais e filme convencional foram usados para avaliar 144 superfícies dentais com e sem cavitação; as radiografias foram analisadas e classificadas em uma escala de 4 pontos. Participaram como examinadores 13 alunos de graduação e um radiologista odontológico. Para validar esta pesquisa foram realizadas análises em microscopia ótica. Os resultados mostraram não haver diferença significante entre os sistemas radiográficos, entretanto, todos tiveram diferenças significantes quando comparados a microscopia óptica, com exceção do sistema Digora® nas superfícies proximais quando o radiologista foi o examinador. Na avaliação interexaminadores, foi obtido concordância moderada, e entre os alunos e o radiologista obteve-se nível sofrível a moderado. Com relação a validade (sensibilidade, especificidade, preditivos positivos e preditivos negativos), os valores foram semelhantes entre os alunos e o radiologista, com exceção dos valores de sensibilidade nas superfícies oclusais. Os estudantes obtiveram um maior numero de resultados falso-positivos e o radiologista odontológico obteve um maior numero de resultados falso-negativos.